2016
DOI: 10.1101/087783
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shifting microbial communities sustain multi-year iron reduction and methanogenesis in ferruginous sediment incubations

Abstract: 19Reactive Fe(III) minerals can influence methane (CH 4 ) emissions by inhibiting microbial 20 methanogenesis or by stimulating anaerobic CH 4 oxidation. The balance between Fe(III) 21 reduction, methanogenesis, and methane oxidation in ferruginous Archean and Paleoproterozoic 22 oceans would have controlled CH 4 fluxes to the atmosphere, thereby regulating the capacity for 23 CH 4 to warm the early Earth under the Faint Young Sun. We studied CH 4 and Fe cycling in 24 anoxic incubations of ferruginous sediment… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Thus, a possible scenario is that Fe(III) is reduced by pyrite oxidation (Eq. 3) (Bottrell et al, 2000), which triggers the "cryptic" sulfur cycle, as observed in other marine sediments (Holmkvist et al, 2011;Brunner et al, 2016;Egger et al, 2016). In this cycle, elemental sulfur, and eventually by disproportionation also sulfide and sulfate, is produced.…”
Section: Potential Methanic Iron Reduction Pathwaysmentioning
confidence: 93%
“…Thus, a possible scenario is that Fe(III) is reduced by pyrite oxidation (Eq. 3) (Bottrell et al, 2000), which triggers the "cryptic" sulfur cycle, as observed in other marine sediments (Holmkvist et al, 2011;Brunner et al, 2016;Egger et al, 2016). In this cycle, elemental sulfur, and eventually by disproportionation also sulfide and sulfate, is produced.…”
Section: Potential Methanic Iron Reduction Pathwaysmentioning
confidence: 93%
“…The sediments were mixed with anoxic freshwater media in a 1:5 ratio in an anoxic chamber and dispensed in stoppered serum bottles, as in Bray et al . (). Cultures were amended first with goethite and later with ferrihydrite.…”
Section: Methodsmentioning
confidence: 97%
“…Two sediment cores were obtained from 590 m water depth in Lake Matano, Sulawesi Island, Indonesia in May 2010 (2°28’S, 121°20’E, in situ sediment temperature ~27°C) and stored under anoxic conditions. The sediments were mixed with anoxic freshwater media in a 1:5 ratio in an anoxic chamber and dispensed in stoppered serum bottles, as in Bray et al (2017). Cultures were amended first with goethite and later with ferrihydrite.…”
Section: Methodsmentioning
confidence: 99%